Sevoflurane causes greater QTc interval prolongation in chronically hyperglycemic patients than in normoglycemic patients. - Seishi Kimura (PLoS ONE, 2017)
QTc interval prolongation is a serious diabetic complication and increases mortality rate. Hyperglycemia inhibits the rapid component of delayed rectifier potassium channel currents (Ikr) and prolongs the QTc interval on electrocardiograms. Sevoflurane also inhibits the Ikr and causes QTc interval prolongation. In fact, torsade de pointes occurred in a patient with poorly controlled diabetes mellitus during sevoflurane anesthesia. We enrolled 74 patients, including 37 normoglycemic patients (glycated hemoglobin [HbA1c]: <6.5%) (NG group) and 37 chronically hyperglycemic patients (HbA1c: ≥6.5%) (HG group). Anesthesia was induced with 2 mg/kg propofol and 0.3 μg/kg/min remifentanil, and maintained with 2% sevoflurane in 40% O2 and 0.2-0.3 μg/kg/min remifentanil. The QT interval and Tp-e interval (from the peak to the end of the T wave) were measured before and at 5, 10, 30, 60, 90, and 120 min after the administration of sevoflurane and adjusted for the patient's heart rate (QTc and Tp-ec, respectively). P-values of <0.05 were considered statistically significant. The QTc and the Tp-ec intervals of the two groups did not differ significantly before the administration of sevoflurane. The QTc interval gradually increased with time in both groups and was significantly longer than the baseline value at 10 min after the administration of sevoflurane in both groups. The QTc interval of the HG group was significantly longer than that of the NG group at 90 min and 120 min after the administration of sevoflurane. The Tp-ec interval was not affected by sevoflurane in either group.We have demonstrated that sevoflurane significantly prolongs the QTc interval, and that the extent of the prolongation is significantly greater in chronically hyperglycemic patients than in normoglycemic patients. Although Tp-ec is not affected by sevoflurane, it should be noted that the simultaneous blockade of potassium channels would increase the risk of arrhythmias.